2019
DOI: 10.1186/s12873-019-0261-2
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature measurement in ambulance: a challenge of 21-st century?

Abstract: Background Some crucial decisions in treatment of hypothermic patients are closely linked to core body temperature. They concern modification of resuscitation algorithms and choosing the target hospital. Under- as well as over-estimation of a patient’s temperature may limit his chances for survival. Only thermometers designed for core temperature measurement can serve as a guide in such decision making. The aim of the study was to assess whether ambulance teams are equipped properly to measure cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…To our knowledge, this is the first report to describe experiences using a forehead continuous deep temperature monitoring system during air evacuation. Podsiad»o et al 4 reported the results of a questionnaire for all 180 operators of the emergency medical system in Poland concerning the number and models of thermometers. There were 1,582 thermometers, and only 3.28% of ground ambulances were able to follow international guidelines regarding a patient's core body temperature precisely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first report to describe experiences using a forehead continuous deep temperature monitoring system during air evacuation. Podsiad»o et al 4 reported the results of a questionnaire for all 180 operators of the emergency medical system in Poland concerning the number and models of thermometers. There were 1,582 thermometers, and only 3.28% of ground ambulances were able to follow international guidelines regarding a patient's core body temperature precisely.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, it is not easy to measure the deep temperature in a prehospital setting because suitable equipment is lacking. 4 Recently, a forehead continuous deep temperature monitoring system was developed (3M Bair Hugger; 3M, St. Paul, MN) (Fig. 1).…”
mentioning
confidence: 99%
“…Because there is no legal provision to equip ambulances with Tc-reading thermometers, it is likely that pre-hospital services are equipped with muchless-expensive, standard medical thermometers able to measure the temperature of the body surface [5]. However, it must be strongly stressed that the temperature of the body surface, mouth, or even that of the auditory canal (especially measured with an infra-red sensor), does not reflect the core temperature [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the patient's BT can be used to guide the selection of an appropriate medical facility [1,4]. However, measuring core BT such as the esophageal temperature is generally unavailable in pre-hospital settings [5]. Axillary temperature is typically used in the out-of-hospital setting; however, this temperature does not necessarily accurately re ect the core BT [6].…”
Section: Introductionmentioning
confidence: 99%